Optimized Synthesis of Ultrahigh-Surface-Area and Oxygen-Doped Carbon Nanobelts for High Cycle-Stability Lithium-Sulfur Batteries. Issue 14 (14th October 2019) - Zou, Jizhao; Niu, Yuan; Tu, Wenxuan; Zhang, Qi; Yao, Yuechao; Zeng, Shaozhong; Lan, Tongbin; Wu, Hongliang; Zeng, Xierong
Abstract : Hierarchical clews of carbon nanobelts (CsCNBs) with ultrahigh specific surface area (2300 m 2  g −1 ) and large pore volume (up to 1.29 cm 3  g −1 ) has been successfully fabricated through carbonization and KOH activation of phenolic resin based nanobelts. The product possesses hierarchically porous structure, three-dimensional conductive network framework, and polar oxygen-rich groups, which are very befitting to load sulfur leading to excellent cycling stability of lithium-sulfur batteries. The composites of CsCNBs/sulfur exhibit an ultrahigh initial discharge capacity of 1245 mA h g −1 and ultralow capacity decay rate as low as 0.162% per cycle after 200 cycles at 0.1 C. Even at high current rate of 4 C, the cells still display a high initial discharge capacity (621 mA h g −1 ) and ultralow capacity decay rate (only 0.039% per cycle) after 1000 cycles. These encouraging results indicate that polar oxygen-containing functional groups are important for improving the electrochemical performance of carbons. The oxygen-doped carbon nanobelts have excellent energy storage potential in the field of energy storage.